The Leadership and Communication Style of the Government of Bojonegoro Regency during the 2018-2023 Period - Bahrul Alam; Agung Dwi Suprayogo; Agus Danugroho (Universitas Muhammadiyah Yogyakarta, 2024)
Each leader has a different communication style in arousing public sympathy for the leader to achieve development goals optimally. In the 2018 regional elections, Dr. Hj. Anna Mu'awanah, M.H., was elected as Regent of Bojonegoro Regency. Since then, during 2018-2023, there have been many changes in governance and development in Bojonegoro Regency. It refers to the communication style of Regent Dr. Hj. Anna Mu'awanah, M.H.'s leadership with the community and government agencies that influence the regent's success in developing his region. The purpose of this research is to determine Dr. Hj. Anna Mu'awanah, M.H as Regent of Bojonegoro for the 2018 - 2023 period in organizing the government she leads and to find out about the governance implemented in the 2018-2023 period in Bojonegoro Regency. This research is a qualitative method. The results indicated that Dr. Hj. Anna Mu'awanah, M.H., the Regent of Bojonegoro, prioritizes innovation and dominates ambition even though she has to sacrifice several matters to carry out her activities. However, this was right on target and was followed by other parties for several common reasons, namely the progress of Bojonegoro Regency. What is meant is giving orders accompanied by goals and objectives regarding the work that must be completed for subordinates. In this way, the regent's communication style, Dr. Anna Mu'awanah, who gave orders with a focus on real action and problem-solving, showed the direction of communication and leadership of the Regent, Dr. Anna Mu'awanah in developing Bojonegoro Regency has been implemented and is under the leadership style indicators according to Stewart L. Tubbs and Selvia Moss (1996). However, there are still several shortcomings in verbal communication to the public.